# How do you solve #(x+4)/3 = (6x)/(-6)#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x+4)/3 = (6x)/(-6), we can start by cross-multiplying to eliminate the fractions. This gives us (-6)(x+4) = (6x)(3). Simplifying further, we get -6x - 24 = 18x. Combining like terms, we have -24 = 24x. Dividing both sides by 24, we find x = -1.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7